The Twin Temptations of Law and Economics - Knudsen, Stefan (2010)
This Note illustrates that the Law & Economics movement (“L&E”) was troubled in its origin, and that those troubles remain. Specifically, as the study of economics evolved, it departed from the study of political economy and the greater concerns for society and was transformed into an inquiry of efficiency alone. In so doing, greater legal relevancy was traded for empirical certainty. This Note also addresses the fundamental problems of L&E as inextricably interwoven with its utilitarian heritage. It argues that L&E is part of a movement that tempts jurists to reach for science and empirical knowledge in an attempt to import certainty and perfection into legal rules. This is not good for the study and practice of law. This Note illustrates that the Law & Economics movement (“L&E”) was troubled in its origin, and that those troubles remain. Specifically, as the study of economics evolved, it departed from the study of political economy and the greater concerns for society and was transformed into an inquiry of efficiency alone. In so doing, greater legal relevancy was traded for empirical certainty. This Note also addresses the fundamental problems of L&E as inextricably interwoven with its utilitarian heritage. It argues that L&E is part of a movement that tempts jurists to reach for science and empirical knowledge in an attempt to import certainty and perfection into legal rules. This is not good for the study and practice of law